2012
DOI: 10.1177/0148607112444756
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Parenteral and Enteral Nutrition Induces Metabolic Dysfunction in Neonatal Pigs

Abstract: Background We previously showed that parenteral nutrition (PN) compared with formula feeding results in hepatic insulin resistance and steatosis in neonatal pigs. The current aim was to test whether the route of feeding (intravenous [IV] vs enteral) rather than other feeding modalities (diet, pattern) had contributed to the outcome. Methods Neonatal pigs were fed enterally or parenterally for 14 days with 1 of 4 feeding modalities as follows: (1) enteral polymeric formula intermittently (FORM), (2) enteral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 65 publications
1
42
0
Order By: Relevance
“…We previously showed that insulin resistance with IL was due to impaired insulin signaling and was associated with increased hepatic inflammation, and thus it was notable in the current study that we found that hepatic Il-6 expression was highest in IL versus OV and SL piglets (40). The explanation for lower hepatic inflammation could be due to the anti-inflammatory and anti-oxidant effects associated with higher liver enrichment of n-3 PUFAs, DHA, and EPA, as well as -tocopherol in the OV and SL versus IL piglets (24,41,42).…”
Section: Discussionsupporting
confidence: 45%
“…We previously showed that insulin resistance with IL was due to impaired insulin signaling and was associated with increased hepatic inflammation, and thus it was notable in the current study that we found that hepatic Il-6 expression was highest in IL versus OV and SL piglets (40). The explanation for lower hepatic inflammation could be due to the anti-inflammatory and anti-oxidant effects associated with higher liver enrichment of n-3 PUFAs, DHA, and EPA, as well as -tocopherol in the OV and SL versus IL piglets (24,41,42).…”
Section: Discussionsupporting
confidence: 45%
“…We and others have established the piglet as an excellent animal model of the term and preterm infant to study the effects of parenteral and enteral nutrition (11)(12)(13)(14). Our fi rst aim was to test whether fi sh oil-containing emulsions compared with soybean oil emulsions can prevent the development of PNALD in preterm, TPN-fed pigs.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…Newborn (Յ1-day-old), crossbred female pigs (n ϭ 6), obtained from the Texas Department of Criminal Justice (Huntsville, TX), were transported to the animal facility of the Children's Nutrition Research Center (Houston, TX). Upon arrival (day 1), piglets were implanted with Silastic catheters in the jugular vein and stomach and a Tygon catheter in the carotid artery as previously described (30). After surgery, piglets were placed in individual cages in a heated room (ϳ30°C) and fed every 3 h at 50% of their requirement for 24 h. Their respective dietary intake was increased gradually to 100% within the next 3 days.…”
Section: Animals and Treatmentsmentioning
confidence: 99%